Characteristics of sputum cellular composition in patients with chronic obstructive pulmonary disease of professional etiology. - V. V. Ivchuk; T. Yu. Kopteva; T. A. Kovalchuk (Medičnì Perspektivi)
Inhalation of high concentrations of various types of dust, in particular of inorganic origin, leads to disruption of the normal mechanism of lung cleaning. A consequence of this is the development of inflammation of the airways with the formation of COPD. The inflammatory response of the airways with exacerbation of COPD is accompanied by the increase in the total number of neutrophils and lymphocytes. This heterogeneous cellular infiltrate is the source of specific biologically active substances that play a significant role in the structural and functional changes in the mucous membrane of the bronchopulmonary system. Sputum formation is one of the main clinical symptoms of respiratory diseases. By the parameters of the cellular composition of sputum, it is possible to determine the pathogenetic variant and the severity of the inflammatory response of the respiratory mucosa. The aim of the work was to study the cellular composition in the spontaneous sputum of COPD patients of mining industry. Cytological and statistical methods of investigation were used to achieve this goal. The study of the characteristics of the cell composition of sputum, depending on the degree of severity of COPD of professional etiology, is relevant and informative and allows to evaluate the activity and role of local inflammation in the development and course of the disease. With an increase in the severity of bronchial obstruction in sputum, the total number of cellular elements, neutrophils and lymphocytes increases. The feature of local inflammation developing in the initial stages of COPD of professional etiology is the predominance of macrophages in sputum. With worsening of the severity of the disease course, when the inflammation acquires a persistent character, the number of neutrophils and lymphocytes increases in sputum.